The Union Convention: An Examination of Limitations on Democratic Decision Making - Anderson, John (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1977)
This article examine a series of factors which may limit the existence of democratic decision making within the union convention.